Proverbs and sayings in Modern English - Sevinc Abdullayeva (Reviews of Modern Science, 2026)
Proverbs are short and unique words and expressions that have been inherited by the people, adopted by the people, and have survived the test of centuries of thought and logic to this day. Proverbs express not only the common feelings and thoughts of the people, but also the common taste of language. It is known to everyone that proverbs hold a very important place in our lives. The use of proverbs in our daily lives, in official situations, and wherever we can think of is inevitable. Proverbs are treasure troves of literature. They have the potential to develop our speech and also have the power of life lessons with their meanings. Proverbs in the vernacular mean the advice given to us by our ancestors, recommendations related to life. We also use these proverbs at certain moments to demonstrate our speech in a rich way. Of course, proverbs belong to all peoples of the world. Some have a counterpart in the Azerbaijani language, while others do not. Different proverbs are used in different moments and situations. For example, “He didn’t look very intelligent, but you can’t judge a book by its cover”. According to its meaning, an opinion about something cannot be formed simply by looking at its external appearance. “Nothing venture, nothing have” - You should try hard to make success, you can’t get anything without risk; the same meaning is used for “You can’t make an omelete without breaking eggs. Meaning, Sometimes men have to do unpleasant things to complete a task or achieve a goal . “The grass is always greener on the other side of the fence” - Meaning, You don’t know about him at all. Maybe he is pretending to be generous / something is more pleasant when it is on the other side. “The rich man’s cock even sets an egg”- Meaning, money comes to the rich people.